Common pulmonary vein atresia: report of three cases and review of the literature. (29th October 2015) - Perez, Michael; Kumar, T. K. Susheel; Briceno-Medina, Mario; Alsheikh-Ali, Mohammed; Sathanandam, Shyam; Knott-Craig, Christopher J.
Abstract: Common pulmonary vein atresia is a rare and usually fatal congenital anomaly, in which the pulmonary veins come together to form a confluence that does not connect to the left atrium. We report our experience with three cases of common pulmonary vein atresia and review the literature on this anomaly. The diagnosis of common pulmonary vein atresia must be entertained in any newborn that presents with cyanosis, refractory acidosis, and decreased systemic perfusion within the first 48 hours of life. Echocardiography is a useful screening tool, but cardiac catheterisation is the preferred diagnostic tool. Common pulmonary vein atresia can be fatal without surgical intervention, but survival after surgery continues to be poor.